2018
DOI: 10.1111/and.12965
|View full text |Cite
|
Sign up to set email alerts
|

Review of the role of leptin in the regulation of male reproductive function

Abstract: Since discovered in 1994, leptin has been thought to be a pleiotropic hormone that regulates food intake, controls energy balance in the body and influences multiple tissues in the body. Leptin plays an important mediating role in the regulation of neuroendocrine and can transmit the nutritional status signals to the reproductive-related central nervous system. Many studies have shown that leptin may play an important role in the control of reproductive function. Leptin can act on all levels of the hypothalamu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 88 publications
(90 reference statements)
0
20
0
Order By: Relevance
“…The relationship between fat mass and puberty may be mediated by several factors, including leptin, the levels of which are very low in our patients. Many animal experiments and human studies have shown that leptin is an important signal in the initiation of puberty (31). Thus, mice or humans who have mutation in leptin gene exhibit central hypogonadism, which is reversed by leptin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between fat mass and puberty may be mediated by several factors, including leptin, the levels of which are very low in our patients. Many animal experiments and human studies have shown that leptin is an important signal in the initiation of puberty (31). Thus, mice or humans who have mutation in leptin gene exhibit central hypogonadism, which is reversed by leptin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A possible positive regulatory effect of resistin on steroidogenic activity in the testicular Leydig cell has been suggested (Roumaud & Martin, 2015). Even though the exact role of leptin on the male reproductive function has not been revealed, it is proposed that leptin would involve in suppression of testicular steroidogenesis (Zhang & Gong, 2018). These findings reflex the existence of a complex regulatory mechanism on the male reproduction by adipocytokines.…”
Section: Discussionmentioning
confidence: 99%
“…To date, we know that leptin plays a crucial role in controlling reproductive function, acting on all levels of the hypothalamusepituitaryegonadal axis, and also may have local effects on the function of testis. 30,31 Leptin and its functional receptor have been detected in prepubertal and adult testes, even though with several differences in cellular localization among species, suggesting the potential for leptin to directly modulate testicular functions. In particular, it has been reported that testicular steroidogenesis as well as germ and Sertoli cell function may be modulated by leptin, either as autocrine/paracrine or endocrine signals.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the past few years several compounds have been described as potential tools to affect leptin-induced cancer growth and progression. 14,27e29 Although leptin and its receptors have been detected in testicular cells, suggesting their direct involvement in testicular functions, 30,31 their expression in human testicular seminoma as well as the role of this adipokine in the development and promotion of testicular seminoma remains largely unknown.…”
mentioning
confidence: 99%